2002
DOI: 10.1081/ddc-120003863
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Plasticizer Molecular Weights and Concentrations on Mechanical and Thermomechanical Properties of Free Films

Abstract: Plasticizers are usually added to improve the mechanical and conditional (thermomechanical) quality of film coatings. Different molecular weights and concentrations of polyethylene glycol were incorporated as plasticizers in hydroxypropylmethylcellulose (HPMC) films. Thermomechanical and mechanical properties of cast films were tested using tensile and dynamic mechanical thermal analysis (DMTA) testing, respectively. The results, as expected, showed that addition of plasticizer caused a decrease in both mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 7 publications
1
24
0
2
Order By: Relevance
“…These changes can be confirmed by TGA results (Fig. 2) as well DMTA measurements, where an increase in the E' modulus is observed [30,31] (Fig. 4).…”
Section: Samples With the Same Glycerol Contentsupporting
confidence: 71%
“…These changes can be confirmed by TGA results (Fig. 2) as well DMTA measurements, where an increase in the E' modulus is observed [30,31] (Fig. 4).…”
Section: Samples With the Same Glycerol Contentsupporting
confidence: 71%
“…This linear relationship between the mechanical properties as a function of the glass transition of films based on biopolymers was previously observed by Honary and Orafai (2002), studying the effect of different molecular weight polyethylene glycols on the mechanical properties of hydroxypropylmethylcellulose films, and by Vanin et al (2005) for films based on pure gelatin plasticized with glycerol, propylene glycol or diethylene glycol. However, Moore et al (2006) showed that the TS of films based on feather keratin and plasticized with glycerol, increased with the T g , following a parabolic trend.…”
Section: Mechanical Propertiesmentioning
confidence: 61%
“…DMA has been reported to be more sensitive to macroscopic as well as molecular relaxation processes compared to other thermal analysis techniques that depend solely on temperature probe (41). It is widely used to determine T g and miscibility between polymers (34,(43)(44). Generally, a dynamic thermal analysis profile may show three forms of transition relaxation.…”
Section: Thermal and Dynamic Mechanical Analysismentioning
confidence: 98%